Incidence, Characteristics and Outcomes of Large Vessel Stroke in COVID-19 Cohort: An International Multicenter Study. (18th December 2021) - Khandelwal, Priyank; Al-Mufti, Fawaz; Tiwari, Ambooj; Singla, Amit; Dmytriw, Adam A; Piano, Mariangela; Quilici, Luca; Pero, Guglielmo; Renieri, Leonardo; Limbucci, Nicola; Martínez-Galdámez, Mario; Schüller-Arteaga, Miguel; et al.
Graphical Abstract: